Pengetahuan, Sikap dan Praktik dengan Penanganan Demam Berdarah Dengue (Journal of Telenursing (JOTING), 2025)
This study aims to explore the description of knowledge, attitudes and practices of handling Dengue Fever in the work area of ​​the Obi Island Clinic. The research design used in this study is descriptive research with a cross-sectional approach. The population in this study were all workers in the work area of ​​the Obi Island Clinic. The sample used in this study was selected based on the sampling method with a purposive sampling type. The instruments used in this study were demographic sheets and questionnaires regarding the Description of Knowledge, Attitudes and Practices with Handling Dengue Fever. Data analysis using a percentage formula for each variable which is then used to determine the cause. The level of knowledge of workers in the good category is 104 respondents (100%). The attitude of workers about DHF in the sufficient category is 101 respondents (97.1%) and the level of practice of workers in the good category is 101 respondents (97.1%). Conclusion, most workers in the Obi Island Clinic Work Area have good knowledge and practices related to DHF, although their attitudes towards DHF are mostly still in the sufficient category. Keywords: DHF, Knowledge, Practice, Attitud